Globally Inclusive Occupational Therapy Scholarship - Bathje, Molly (The open journal of occupational therapy, 2025)
Occupational therapy is a global profession and OJOT supports global scholarship through its open-access, online format. OJOT is read in over 200 countries and global/international authorship is encouraged. This article describes the global reach of OJOT and suggests how OJOT authors can embrace the opportunity and responsibility of producing scholarship that has the potential for global impact. Keywords scholarship, global, occupational therapy